MORPHOLOGICAL FEATURES OF THE TESTES AND EPIDIDYMIS OF RATS AFTER THEIR EXPOSURE TO ELECTROMAGNETIC FIELD OF HIGH VOLTAGE AND LOW FREQUENCY - Топка, Е.Г.; Шарапова, О.М. (World of Medicine and Biology, 2014)
In modern conditions of the active development of the industry in Ukraine, in particular, in the Dnepropetrovsk region, the problem of environmental pollution has taken on special significance. One of the harmful factors, that negatively affect the people in the working rooms of power plants and steel mills, is a low-frequency electromagnetic field. The authors of this study made an attempt to solve the problem of determination of the morphological changes in the microvasculature of the testes of rats exposed to electromagnetic field of high voltage and low frequency. As a material for the study 56 adult male albino rats were used, they were divided into 2 groups: I group - control (10 rats); Group II - animals that were exposed to an electromagnetic field with a voltage of 750 kV and a frequency of 50 Hz at the substation "Dnepropetrovsk" in Dnepropetrovsk city for 14, 30, 45, 90 and 120 days every day for 1.5 hours (46 rats). The animals were then taken out of the experiment by cervical dislocation under ether anaesthesia. Histological specimens stained with haematoxylin-eosin were prepared using testicular tissue. Stained sections of organs were studied in binocular microscope "Leica CME" and the light microscope "Biola". The researchers found that the testes of rats under macroscopic examination had the same shape and color in all the series. Structural organization of sections has been saved. There was no cellular infiltration. Oval shaped convoluted tubules remained firmly attached to each other. On the inner side of the basal membranes, which in all the series retained their integrity, there were bright and dark spermatogonias. The nuclei were round in shape and were not pyknotic. The light and dark sustentocites, located between the spermatogonias, reached the tops of their tubular lumen. These cells had a pyramidal shape and nuclei of irregular shape. Cytoplasm and the nucleus had no degenerative changes. On the lateral surfaces of the cytoplasm were bay-like lacunas, which adjoined cells of spermatogenesis. Between neighbouring sustentocytes areas of tight connections remained preserved. Spermatogenesis was preserved in all the series of experiments, the lumen of the tubules contained spermatozoony emanating from the tops of sustentocytes tails forward. There were no young or overripe forms. In the normal range, compared with the control group, there were isolated pathological forms with double head and tail, and a deviation of the neck or tail. Interstitial tissue showed no signs of proliferation and was moderately oedematous under a protein membrane within 120 days after exposure. On the slices of over-testis in all series of experiments cellular infiltration was not noted. Adventitia of the excretory ducts of the head and over-testis ducts in the body and tail showed no signs of oedema. Cells of muscle-fibrous layer had no degenerative changes of the cytoplasm and the nucleus. Desquamation of epithelial cells was not noted. The structure of a double-row epithelium is fully preserved. Between the basal portions of the prismatic cells with homogeneous round nuclei, small round shape interneurons with rounded nuclei were observed. Degenerative changes in the cytoplasm and nuclei of the epithelium were not noted throughout the whole time of exposure to radiation. There were spermatozoons in the lumen of the duct. After conducting this study, the authors concluded, that in terms of the exposure of animals to the electromagnetic field for the time of 14 to 120 days, morphological changes in the testis are shown as a reduction in the number of the convoluted seminiferous tubules, increase in interstitial tissue content, reduction of the diameter of the convoluted seminiferous tubules, degeneration of the germinal epithelium, the appearance of pathological forms of seminiferous epithelium at all stages of development.